The Contribution of Self-Involvement and Social Rejection to Social Change Perception - Juneman Abraham; Bagus Takwin (ANIMA Indonesian Psychological Journal, 2017)
Eibach, Libby, and Gilovich’s (2003) experimental research suggested that people with less self-change awareness will perceive that their social worlds change more than do those who are more aware that they themselves are changing. This present review, based on two other studies, serves as a further research recommendation to expand their thesis. Social cognition experiments conducted by Cloutier and Macrae (2008) as well as by Hess and Pickett (2010) using the social memory paradigm indicated that if a person experiences: (1) personal disengagement (self-univolvement, i.e. his/her experience is chosen by others); and (2) social rejection, then he/she will be less aware of him/herself, and will remember more (or is more aware of) information regarding other people (others > self). Reversely, a person with: (1) self-involvement (i.e. selects his/her own experience); and (2) social acceptance experience, will be more aware of him/herself than of others (self > others) and will perceive the social world to change less. Based on those findings, the authors hypothesize that self-involvement and social rejection–as variables that influence the awareness of self (changes)–influence one’s perception of social changes. Some applications related to colonial mentality, as well as Bitcoin and blockchain technology, are presented as illustrations to elaborate the conjecture.